2013
DOI: 10.1371/journal.pone.0066492
|View full text |Cite
|
Sign up to set email alerts
|

Native Prey and Invasive Predator Patterns of Foraging Activity: The Case of the Yellow-Legged Hornet Predation at European Honeybee Hives

Abstract: Contrary to native predators, which have co-evolved with their prey, alien predators often benefit from native prey naïveté. Vespa velutina, a honeybee predator originating from Eastern China, was introduced into France just before 2004. The present study, based on video recordings of two beehives at an early stage of the invasion process, intends to analyse the alien hornet hunting behaviour on the native prey, Apis mellifera, and to understand the interaction between the activity of the predator and the prey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 69 publications
6
75
3
2
Order By: Relevance
“…Unlike findings described for Vespa tropica [40], Vespa velutina and Vespa crabro [41], we never observed V . germanica capturing foragers in flight returning to the hive, despite being easy prey because they are weighed down by nectar or pollen load, and “tired” after the flight activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike findings described for Vespa tropica [40], Vespa velutina and Vespa crabro [41], we never observed V . germanica capturing foragers in flight returning to the hive, despite being easy prey because they are weighed down by nectar or pollen load, and “tired” after the flight activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the number of nests continued to increase in our study area from year to year since the first appearance of V. velutina in 2007, which suggested that the carrying capacity of the area (i.e., the overall resource availability in support of nesting and/or food sources) was not reached yet. Indeed, V. velutina forms large colonies that produce thousands of individuals that require huge quantities of proteins, which explained the impressive predation pressure on honeybee colonies (Monceau et al ., ,b; ). Therefore, the carrying capacity of the environment may yet affect the number of nests.…”
Section: Discussionmentioning
confidence: 98%
“…The yellow‐legged hornet, Vespa velutina , was first observed in France in 2004 and has since proliferated throughout the French territory, with spread also into Spain and Portugal and more recently, into Italy (Monceau et al ., ; Arca et al ., ). The invasion of this hornet species causes several ecological, economic and public health problems, with predation on domestic honeybees as the most obvious current problem (Monceau et al ., ,b; Arca et al ., ). In addition to the effect on bees as pollinators, V. velutina is also a source of stress for beekeepers and has a clear, critical effect on the professional activities of small beekeepers (Monceau et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, only direct observations or video records have allowed monitoring the activity of V. velutina (Monceau, Arca, et al., 2013 2017; Monceau, Bonnard, et al, 2013; Monceau et al., 2017; Perrard, Haxaire, Rortais, & Villemant, 2009). Our results are in line with these previous studies.…”
Section: Discussionmentioning
confidence: 99%